Impacts of CAD/CAM Metallic Materials on Trace Metals and Biocompatibilities: An in vivo Study in Beagle Dogs - Lin, Yunzhi; Chen, Jinbing; Jiang, Fangke; Pan, Yu; Xu, Caiming; Lin, Donghong; Lin, Honglei; Jiang, Lei; Zheng, Dali; Qiu, Jing; Cheng, Hui (Frontiers in Materials, 2021)
CAD/CAM (computer-aided design and computer-aided manufacturing) technology has been widely applied in clinical dentistry, but the material safety remains a concern. To investigate the impacts of CAD/CAM metallic materials on trace metals and biocompatibilities, selective laser melted (SLM) cobalt-chromium (Co-Cr) alloys and computer numeric controlled milled (CNC milled) commercially pure titanium (CP-Ti) were placed on the maxilla of beagle dogs for 6 months. The trace metals in the oral mucosa, blood, liver, kidney, and hair were then determined by inductively coupled plasma mass spectrometry (ICP-MS). The histopathologic changes and biocompatibilities of tissues were examined by hematoxylin and eosin (H&E) staining, terminal deoxynucleotidyl transferase (TdT)-mediated dUTP-digoxigenin nick end labeling (TUNEL) method, immunohistochemistry (IHC) assay, Western blot analysis, and liver and kidney function tests. Our results showed that trace metals released from these two CAD/CAM metallic materials accumulated transiently in the oral mucosa and whole blood. The trace metals released from SLM Co-Cr alloys could also transiently accumulate in the plasm and hair. In addition, these two CAD/CAM metallic materials both induced apoptosis and histopathologic changes in the oral mucosa, with SLM Co-Cr alloys inducing a higher level of apoptosis. In contrast, both materials did not exert autophagic effects on the oral mucosa or affect the trace metals, functions, or biocompatibilities of the liver and kidney. Therefore, this study suggests that CAD/CAM metallic materials should be selected carefully, especially in patients with metal- and apoptosis-related diseases, and CNC-milled CP-Ti can be recommended to patients on account of its better biocompatibility and safety.